Thalamic volume in very preterm infants: associations with severe brain injury and neurodevelopmental outcome at two years - Trimarco, Emiliano; Jafrasteh, Bahram; Jiménez-Luque, Natalia; Marín Almagro, Yolanda; Román Ruiz, Macarena; Lubián Gutiérrez, Manuel; Ruiz González, Estefanía; Segado Arenas, Antonio; Lubián-López, Simón Pedro; Benavente-Fernández, Isabel (Frontiers in Neurology, 2024)
Introduction Several studies demonstrate the relationship between preterm birth and a reduced thalamus volume at term-equivalent age. In contrast, this study aims to investigate the link between the thalamic growth trajectory during the early postnatal period and neurodevelopment at two years of age. Methods Thalamic volume was extracted from 84 early MRI scans at postmenstrual age of 32.33 (± 2.63) weeks and 93 term-equivalent age MRI scans at postmenstrual age of 42.05 (± 3.33) weeks of 116 very preterm infants (56% male) with gestational age at birth of 29.32 (± 2.28) weeks and a birth weight of 1158.92 (± 348.59) grams. Cognitive, motor, and language outcomes at two years of age were assessed with Bayley Scales of Infant and Toddler Development Third Edition. Bivariate analysis was used to describe the clinical variables according to neurodevelopmental outcomes and multilevel linear regression models were used to examine the impact of these variables on thalamic volume and its relationship with neurodevelopmental outcomes. Results The results suggest an association between severe brain injury and thalamic growth trajectory (β coef = −0.611; p < 0.001). Moreover, thalamic growth trajectory during early postnatal life was associated with the three subscale scores of the neurodevelopmental assessment (cognitive: β coef = 6.297; p = 0.004; motor: β coef = 7.283; p = 0.001; language: β coeficient = 9.053; p = 0.002). Discussion These findings highlight (i) the impact of severe brain injury on thalamic growth trajectory during early extrauterine life after preterm birth and (ii) the relationship of thalamic growth trajectory with cognitive, motor, and language outcomes.